The Guest House - Morgan-Bentley, Robin (Naperville : Poisoned Pen Press, 2022)
"An unputdownable thriller with an "oh shit!" beginning for readers of Ruth Ware and Lucy Foley that finds Jamie and Victoria, a married couple expecting their first baby, locked inside the guesthouse they were visiting on vacation just as Victoria feels contractions starting"--.
new book 2022 fall.
Keywords: Pregnancy; Imprisonment; Thrillers; Novels; Thriller fiction